Calcined reason: review of teatro Amazonas, by the company Azkona & Toloza - Santos, Valmir Jesus dos (Sala Preta, 2023)
The show denounces the promiscuous and historical compliance of governments and private initiative with illegal extractivist activities, drivers of the environmental crisis in the Amazon, a biome that has 60% of its extension in the north of Brazil. It is eye-catching by using audiovisual documentary procedures, verbatim technique, and animated forms that gain sensory dimensions. There is an intrinsic logic in terms of expanded dramaturgy, like the confluence of volumes, lights, shadows, and objects that little by little transform the stage into a sculptural installation.